Nanorepairers Rescue Inflammation‐Induced Mitochondrial Dysfunction in Mesenchymal Stem Cells. Issue 4 (11th December 2021) - Zhai, Qiming; Chen, Xin; Fei, Dongdong; Guo, Xiaoyan; He, Xiaoning; Zhao, Wanmin; Shi, Songtao; Gooding, John Justin; Jin, Fang; Jin, Yan; Li, Bei
Abstract: Mitochondrial dysfunction in tissue‐specific mesenchymal stem cells (MSCs) plays a critical role in cell fate and the morbidity of chronic inflammation‐associated bone diseases, such as periodontitis and osteoarthritis. However, there is still no effective method to cure chronic inflammation‐associated bone diseases by physiologically restoring the function of mitochondria and MSCs. Herein, it is first found that chronic inflammation leads to excess Ca 2+ transfer from the endoplasmic reticulum to mitochondria, which causes mitochondrial calcium overload and further damage to mitochondria. Furthermore, damaged mitochondria continuously accumulate in MSCs due to the inhibition of mitophagy by activating the Wnt/ β ‐catenin pathway under chronic inflammatory conditions, impairing the differentiation of MSCs. Based on the mechanistic discovery, intracellular microenvironment (esterase and low pH)‐responsive nanoparticles are fabricated to capture Ca 2+ around mitochondria in MSCs to regulate MSC mitochondrial calcium flux against mitochondrial dysfunction. Furthermore, the same nanoparticles are able to deliver siRNA to MSCs to inhibit the Wnt/ β ‐catenin pathway and regulate mitophagy of the originally dysfunctional mitochondria. These precision‐engineered nanoparticles, referred to as "nanorepairers, " physiologically restore the function of mitochondria and MSCs, resulting in effective therapy for periodontitis and osteoarthritis. The concept can potentially be expanded to the treatment of other diseases via mitochondrial quality control intervention. Abstract : Chronic inflammation leads to mitochondrial Ca 2+ overload and the inhibition of mitophagy, resulting in the impaired differention of mesenchymal stem cells (MSCs). Based on mechanistical findings, precision‐engineered nanoparticles physiologically restore the function of mitochondria and MSCs by capturing Ca 2+ around mitochondria and inhibiting Wnt/ β ‐catenin pathway, providing effective therapy for periodontitis and osteoarthritis.